PENGARUH STORE ATMOSPHERE, LOKASI DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA LANGKAH COFFEE SHOP - Putu Vriska Andria Dewi; Anak Agung Putu Agung; I Made Surya Prayoga (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2021)
In today's business era, competition in the business world is getting tighter. Companies must strive to study and understand the needs and wants of their customers, so as to create a sense of satisfaction for customers. This study aims to determine the effect of store atmosphere, location and service quality on customer satisfaction. Coffee Shop Steps. The population of this research is consumers who make purchases at the Step Coffee Shop. The sampling technique used a purposive sampling method. The data analysis technique used to test the deep hypothesis is multiple linear regression analysis. The results showed that the store atmosphere, location and service quality had a positive and significant effect on customer satisfaction. Coffee Shop Steps. Further researchers are expected to add variables other than store atmosphere, location and service quality, because there are still other factors that can affect customer satisfaction.